Nurse’s Experience in Caring End-of-Life Patients in Intensive Care Unit RSPI Prof. Dr Sulianti Saraso Jakarta Year 2021 - Puguh E Mintarto; Achmad Fauzi (STIKep PPNI Jawa Barat, 2022)
Aims: To explore nurse's experience in caring of end-of-life patients in intensive care unit rspi prof. Dr sulianti saraso jakarta year 2021 Design: The type of research used in this research is qualitative research with a phenomenological approach Methods : The subjects in this study were fiven nurses in the ICU RSPI Prof. Dr. Sulianti Saroso. Data analysis was carried out with the stages of data reduction, data presentation and leverage. Results: Based on the results of research interviews, we found four three themes as follow: 1) Nurses have good mastery; 4) Nurse emotional control; 3) Nurse response toward end-of-life care. Conclusions: This study found that nurse experience positively while caring of patients in end-of-life care, even sometime they still need to control their emotion of being empathy to the patients’ condition. Comprehensive and continue training related to end of life care is require to enhance and update nurse knowledge and skill of end-of life care.